2008
DOI: 10.1038/ng.211
|View full text |Cite
|
Sign up to set email alerts
|

Kras regulatory elements and exon 4A determine mutation specificity in lung cancer

Abstract: KRASis the most frequently mutatedrasfamily member in lung carcinomas 1,2 , whereasHRASmutations are common in tumours from stratified epithelia such as bladder or skin (www.sanger.ac.uk/genetics/CGP/cosmic/). Using a mouse model (HrasKI) 3 in which theHrascoding sequence was inserted into theKraslocus, we demonstrate that specificity forKrasmutations in lung andHras mutations in skin tumours is determined by local regulatory elements in the targetrasgenes. We further show that, whileKras-4Ais dispensable for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
124
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(130 citation statements)
references
References 27 publications
(55 reference statements)
5
124
0
1
Order By: Relevance
“…However, a similar study using a mouse genetic model to induce colon carcinomas showed no such effect of K-Ras4A deficiency (27). Another study using a different mouse transgenic at the KRAS locus revealed a role for K-Ras4A in tumorigenesis: when the cDNA sequence of K-Ras4B was knocked into the KRAS locus, such that only K-Ras4B could be expressed (designated KRAS KI ), homozygous KRAS KI mice were resistant to urethane-induced lung carcinogenesis (14). However, the same study called into question the protumor effects of WT K-Ras4A by showing that, when the KRAS KI allele was heterozygous with the KRAS LA2 allele that spontaneously recombines to generate oncogenic K-Ras, more lung tumors developed in KRAS KI/LA2 than KRAS wt/LA2 mice, consistent with a tumor suppressor effect of WT K-Ras4A (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a similar study using a mouse genetic model to induce colon carcinomas showed no such effect of K-Ras4A deficiency (27). Another study using a different mouse transgenic at the KRAS locus revealed a role for K-Ras4A in tumorigenesis: when the cDNA sequence of K-Ras4B was knocked into the KRAS locus, such that only K-Ras4B could be expressed (designated KRAS KI ), homozygous KRAS KI mice were resistant to urethane-induced lung carcinogenesis (14). However, the same study called into question the protumor effects of WT K-Ras4A by showing that, when the KRAS KI allele was heterozygous with the KRAS LA2 allele that spontaneously recombines to generate oncogenic K-Ras, more lung tumors developed in KRAS KI/LA2 than KRAS wt/LA2 mice, consistent with a tumor suppressor effect of WT K-Ras4A (14).…”
Section: Discussionmentioning
confidence: 99%
“…Another study using a different mouse transgenic at the KRAS locus revealed a role for K-Ras4A in tumorigenesis: when the cDNA sequence of K-Ras4B was knocked into the KRAS locus, such that only K-Ras4B could be expressed (designated KRAS KI ), homozygous KRAS KI mice were resistant to urethane-induced lung carcinogenesis (14). However, the same study called into question the protumor effects of WT K-Ras4A by showing that, when the KRAS KI allele was heterozygous with the KRAS LA2 allele that spontaneously recombines to generate oncogenic K-Ras, more lung tumors developed in KRAS KI/LA2 than KRAS wt/LA2 mice, consistent with a tumor suppressor effect of WT K-Ras4A (14). Thus, the literature on K-Ras4A-deficient mice provides little clarity and no mechanistic understanding of any biological differences that may distinguish the two highly conserved splice variants of the KRAS locus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The molecular mechanism for cell-type specificity for activating mutations of particular RAS genes has recently been proposed to be determined, at least in part, by the expression levels of the individual RAS genes. Thus, urethane induces lung cancers that are associated with Kras mutations in mice, but when an Hras cDNA is knocked into the Kras gene locus, and is thus expressed under the control of the Kras gene promoter, the urethane-induced tumors harbor Hras mutations instead (5). However, there is also evidence that distinct membrane targeting of the different Ras proteins may confer them with specific functions (6).…”
mentioning
confidence: 99%
“…It has been shown that KRAS4A plays an essential role in the development of carcinogen-induced lung cancer in mice and that oncogenic KRAS4A is widely expressed in human cancers (46,47). Suppression of palmitoylated RAS signaling is, therefore, likely to be an effective therapeutic strategy for a broad range of cancers.…”
Section: Discussionmentioning
confidence: 99%